"Coal Rush" and the Donets Basin industrial development: leakage events creators - Gennadiy Gayko; Volodymyr Biletsky (Cхід)
The question of the Donets Basin industrial development, including the formation and development of the coal and steel industry, which in the second half of the nineteenth century - the beginning of the twentieth century. Briefly describe the most important events and contributions of Ukrainian and foreign researchers and entrepreneurs in the industrial transformation in eastern Ukraine.